NON–LINEAR DEPRECIATION. - Carman, Lewis A. (The Accounting Review, 1956)
This article focuses on non-linear depreciation in accounting. The depreciation of a physical asset is its decline in value by the action of deleterious or adverse factors. These generally are wear-and-tear, the elements, neglect, and so on, but may also include obsolescence and other nonphysical factors. The basic problem of accounting for depreciation is the selection of the systematic manner in which the cost of the asset is to be written off over its useful life. The value of the asset declines from its initial value at the beginning of its useful life to a terminal value at the end thereof. This terminal value may be either zero or a residual value commonly termed the scrap value. The problem is to state the residual or depreciated value of the asset at any selected point during its life. There are two general types of continuous functions available for depreciation computations, the rectilinear and the curvilinear. The facts of curvilinear depreciation will be formulated herein in such a manner that anyone desirous of utilizing such a scheme for the computation of depreciation need only substitute the basic data of the problem in a formula.